2011
DOI: 10.3390/toxins3091131
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mannose Receptor (CD206) in Innate Immunity to Ricin Toxin

Abstract: The entry of ricin toxin into macrophages and certain other cell types in the spleen and liver results in toxin-induced inflammation, tissue damage and organ failure. It has been proposed that uptake of ricin into macrophages is facilitated by the mannose receptor (MR; CD206), a C-type lectin known to recognize the oligosaccharide side chains on ricin’s A (RTA) and B (RTB) subunits. In this study, we confirmed that the MR does indeed promote ricin binding, uptake and killing of monocytes in vitro. To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…While these studies support a role of the MR in promoting toxicity of ricin in vivo, recent results from ricin challenge studies of MR deficient mice revealed the opposite outcome. MR knockout mice proved to be more sensitive to ricin-induced death than their wild-type counterparts, which is consistent with a role for the MR in clearance and degradation of ricin toxin, and not enhancement of toxin uptake (Gage et al 2011). The MR will not be discussed further in this chapter.…”
Section: Ricin Toxicity Structure and Functionsupporting
confidence: 63%
“…While these studies support a role of the MR in promoting toxicity of ricin in vivo, recent results from ricin challenge studies of MR deficient mice revealed the opposite outcome. MR knockout mice proved to be more sensitive to ricin-induced death than their wild-type counterparts, which is consistent with a role for the MR in clearance and degradation of ricin toxin, and not enhancement of toxin uptake (Gage et al 2011). The MR will not be discussed further in this chapter.…”
Section: Ricin Toxicity Structure and Functionsupporting
confidence: 63%
“…Mannosylated-mediated processing is commonly associated with endocytic trafficking towards recycling mechanisms (to refresh surface CD206)[42] and through proposed additional endocytic vesicles (early to late endosome)[43]. Whereas, other studies have indicated that general phagocytosis does not contribute significantly to biomolecule release, representing less than 5% of processed cargo[44]. Thus, mannosylation of PBAEs is clearly triggering uptake and processing mechanisms beneficial to eventual gene delivery.…”
Section: Resultsmentioning
confidence: 99%
“…MR receptor is expressed on a variety of monocyte derived cell populations including alternatively activated M2 macrophages and dendritic cells 49 . There is also evidence that MR is present on monocytes as ricin toxin induced apoptosis of THP-1 monocytes can be attenuated with anti-MR antibodies 50 . Lesion localized MR expressing macrophages do not associate with lipids and do not transition into foam cells 51 , suggesting they are serving a non-traditional function within the plaques, possibly recruited to the region by the mannose residues on the luminal surface.…”
Section: Discussionmentioning
confidence: 99%